Abnormal magnetoresistance behavior in Nb thin films with rectangular arrays of antidots - 张伟君 何世坤 李博宏 程飞 许兵 温振超 曹文会 肖宏 韩秀峰 赵士平 邱祥冈 (Chinese physics B, 2012)
Magnetoresistance in superconducting Nb films perforated with rectangular arrays of antidots （holes） is investigated at various temperatures and currents. Normally, the magnetoresistance increases with the increasing magnetic field. In this paper, we report a reverse behavior in a certain range of high fields after vortex reconfiguration transition, where the resistances at non-matching fields are smaller than those in the low field regime. This phenomenon is due to a strong caging effect, in which the interstitial vortices are trapped among the pinned multiquanta vortices. This effect is temperature and current dependent.